The Influence of Succession Planning on Staff Performance among County Government Employees in Kenya: A Study of Baringo County Government - Kimeli M. Chirchir; Isaac Koros (International Journal of Marketing & Human Resource Research, 2021)
Devolution of resources in County Governments was to ensure resources reach the citizens. However, staff performance has continuously been affected by the change in both leadership and senior successors in the County Governments necessitating the need to examine the influence of succession planning on staff performance in County Governments. The study sought to establish the effect of career development planning, selection planning and human resource planning on staff performance in Baringo County.  Anchored on Scharmer’s U-Theory, the study adopted descriptive research design on a target population of 14 executive employees and 57 middle-level managers through a questionnaire instrument. Descriptive and inferential statistics were used to analyze data; descriptive statistics optimized mean and standard deviation while ANOVA was used to produce variables relationships.  The study findings revealed the County Governments provided training through seminars and workshops. Benchmarking was often done to improve the skills of employees. It was also found that mentorship programs were also offered for staff to do new roles. These while preparing staff to take higher roles influenced performance of the staff.  The selection planning through internal and external selection was also found to affect performance of staff. Similarly, human resource planning had a significant effect on staff performance. The County had policies that reduced the retrenchment of employees.    The County did practice performance appraisals, promoted performing employees and had an independent County Public Service Board. Evidencing the existence of a somewhat abstract succession plan. The study recommended the county government should ensure the existence and operationalization of a robust succession management plan that anchors career development programs.